Analysis of Public Awareness and the Principles of Good Corporate Governance on Customer Trust in Bank Syariah Indonesia Padangsidimpuan Branch - Nur Cahaya Siregar; Rosnani Siregar; Purnama Hidayah Harahap (Journal of Management, Entrepreneurship, and Tourism, 2026)
Based on data from the Financial Services Authority (OJK), Islamic banking has continued to expand and become an integral component of Indonesia's financial system, although the level of Islamic financial literacy remains lower than that of conventional finance. This study aims to examine the effects of public awareness and Good Corporate Governance on customer trust at Bank Syariah Indonesia Padangsidimpuan Branch. A quantitative approach with a causal associative research design was employed. The study involved 100 customers selected through purposive sampling, and data were collected using a structured questionnaire with a five-point Likert scale. Data were analyzed using validity, reliability, and normality tests, followed by multiple linear regression, t-test, F-test, and coefficient of determination (R²). The findings indicate that public awareness has a positive and significant effect on customer trust. In contrast, Good Corporate Governance does not have a significant partial effect on customer trust. However, public awareness and Good Corporate Governance jointly exert a significant influence on customer trust. The coefficient of determination shows that both independent variables explain 78.4% of the variance in customer trust, while the remaining 21.6% is attributable to factors beyond the scope of this study. These findings highlight the importance of strengthening Islamic financial literacy alongside governance practices to foster sustainable customer trust in Islamic banking.